Evaluation of an innovative programme for training teachers of children with learning and behavioural difficulties in New Zealand*. Issue 3 (27th May 2017) - Pilgrim, Marcia; Hornby, Garry; Everatt, John; Macfarlane, Angus
Abstract: This article reports the views of recent graduates of a competency based, blended learning teacher education programme for specialist resource teachers of children with learning and behaviour difficulties in New Zealand. Identifying and developing the competencies needed by teachers in the field of special needs education is important in ensuring that these specialists are well prepared to meet the needs of students and schools. Participants completed an online questionnaire survey responding to two questions, the extent to which the 51 competencies addressed in the programme were important to their professional work, and the extent to which the programme had enabled them to develop these competencies. Results indicated that programme competencies were perceived by participants to be of high importance to their work in the field of learning and behaviour difficulties, and that they considered themselves to have been well enabled to develop these competencies. Based on these findings, implications for teacher educators are discussed, limitations of the research study are identified and recommendations for future research made.